Simulation of Efficiency in Improving the Performance of Cylindrical Vertical Furnace Using Indirect Method - Dimas Adhitya Rahman; Ismiyati Ismiyati; Tri Yuni Hendrawati (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2022)
One of the essential pieces of equipment at the Pertamina Refinery Unit V Balikpapan is the Furnace F-3-04 Vertical Cylindrical type. Furnace operation efficiently becomes very important given the vast energy consumption and directly influences the level of refinery profits. Therefore, it is necessary to do a simulation to increase the efficiency value to minimize energy use. This study aimed to determine the effect of O2 Excess and Flue Gas temperature on efficiency and to find the best efficiency from the simulation results on a Vertical Cylindrical Furnace. In this study, the furnace's efficiency is calculated and simulated using the indirect method. The heat entering the furnace is reduced by the heat lost compared to the heat entering. Initial data processing is a normality test to determine whether the data is usually distributed and can be used for data to be entered into the mathematical simulation of furnace efficiency. The efficiency value produced by Furnace F-3-04 is 86.3%, with an O2 excess value of 7.25% and a Flue Gas temperature of 419 0C. From the simulation carried out, it can be seen that the operating parameter that most affects efficiency is O2 Excess of 0.15 – 0.18% for every 0.5% decrease in O2 Excess for 5 simulations. Meanwhile, the Flue Gas temperature gets a value of 0.02 – 0.03% for every 2 0C decrease for 5 simulations. The best efficiency value is 87.7%, with O2 Excess of 4.75% and Flue Gas temperature of 409 0C.